Three-Dimensional Numerical Analysis of Compound Lining in Complex Underground Surge-Shaft Structure. (19th May 2015) - Chen, Juntao; Yang, Yang; Ye, Chao; Yang, Ying; Xiao, Ming
Abstract : The mechanical behavior of lining structure of deep-embedded cylinder surge shaft with multifork tunnel is analyzed using three-dimensional nonlinear FEM. With the elastic-plastic constitutive relations of rock mass imported and the implicit bolt element and distributed concrete cracking model adopted, a computing method of complex surge shaft is presented for the simulation of underground excavations and concrete lining cracks. In order to reflect the interaction and initial gap between rock mass and concrete lining, a three-dimensional nonlinear interface element is adopted, which can take into account both the normal and tangential characteristics. By an actual engineering computation, the distortion characteristics and stress distribution rules of the dimensional multifork surge-shaft lining structure under different behavior are revealed. The results verify the rationality and feasibility of this computation model and method and provide a new idea and reference for the complex surge-shaft design and construction.